Taxonomic placement of selected plant pathogenic fungi revisited: Acroconidiella, Ceratobasidium lantanae-camarae, Duosporium, Korunomyces and Perisporiopsidaceae - Ferreira, Bruno Wesley (2021)
Since the early days of mycology, the classification of fungi has been based mainly on morphological characters, with substrate, geographical distribution, chemotaxonomic or ecological information playing a complementary role for some groups. This, sometimes, resulted in provisional or dubious sytems of classification and to incorrectly assumed affinities and mistaken application of names to fungal taxa. With the advent of molecular biology and its incorporation in the polyphasic approach for the taxonomy of fungi, it became progressively possible to better elucidate the relationships between members of the Kingdom Fungi and to erect a more reliable and natural system of classification of these organisms. A taxonomic reassessment of selected taxa of plant pathogenic fungi, ranging from species to families, was conducted based on specimens recollected in Brazil. Obtaining pure cultures of these fungi allowed for extraction and sequencing of DNA regions and to address the key issue of the phylogenetic affinities and correct application of names for those fungi. Among the specimens recollected during this study some were selected and indicated as neotypes or epitypes for taxa which were erected in the past. The reexamination of morphological features was carried out, as well as the obtaining of molecular information, enabled, for the first time, the application of the polyphasic approach to these taxa. As a result, the following taxa were “debunked”: family Perisporiopsidaceae (considered a synonym of Phaeosphaeriaceae); the genera Acroconidiella (found to be a late synonym of Alternaria), Duosporium (syn. of Curvularia) and Korunomyces (syn. of Coniella). Ceratobasidium lantanae-camarae, was found to be distinct from C. cornigerum – to which it was mistakenly synonymized – and reinstated. Taxonomic novelties were treated, as determined by the present nomenclatural rules, for publication. Keywords: Phylogeny. Fungi. Taxonomy.